a-b=6,b-c=3,则a²-c²+2b(c-a)等于多少
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/02 23:32:49
a-b=6,b-c=3,则a²-c²+2b(c-a)等于多少a-b=6,b-c=3,则a²-c²+2b(c-a)等于多少a-b=6,b-c=3,则a²
a-b=6,b-c=3,则a²-c²+2b(c-a)等于多少
a-b=6,b-c=3,则a²-c²+2b(c-a)等于多少
a-b=6,b-c=3,则a²-c²+2b(c-a)等于多少
a-b=6,
b-c=3
a-c=9,a+c-2b=3
a²-c²+2b(c-a)=(a-c)[a+c-2b]=9×3=27
a方-c方=(a-c)(a+c)
整个式子就是:(a-c)(a+c-2b)=(a-b+b-c)【a-b-(b-c)】=(3+6)*(6-3)=27
a²-c²+2b(c-a)=(a²-2ab+b²)-(b²-2bc+c²)=(a-b)²-(b-c)²=36-9=27
27
因a-b=6,b-c=3故两个相加得 a-c=9, 两个相减得 a+c=3+2b 而a2-c2+2b(c-b)=(a+c)(a-c)-2b(a-c) 代入得到(3+2b)9-2b9=27完.
6*3=a(b-c)-b(b-c). 18=ab-ac-bb+bc. a²-c²+2b(c-a) =aa-cc+2bc-2ba = a-b-b+c=3.~a+c-2b=3.~a+c=3+2b. a-b+b-c=9.~a-c=9.~c-a=-9 原式=(3+2b)*9+2b(-9). =27+18b-18b =27. 完毕